New Geographical Record of the Lizard Phymaturus williamsi Lobo et al., 2013 (Squamata: Liolaemidae) After a Decade of Its Description in the Puna Region of Argentina - Valdez Ovallez, Franco Miguel (2025)
The species of the genus Phymaturus are viviparous, inhabit rocky areas in cold and harsh environments, and are characterized by restricted distributions with a high level of endemism. The objective of this work is to report a new geographic record of Phymaturus williamsi and expand its known distribution within the Province of San Juan, Argentina. In February 2023, during faunal sampling in the Calingasta Department, three adult male specimens of P. williamsi were observed. This new record is located approximately 32 km southwest in a straight line from the species’ type locality. Additionally, the straight-line distance to its closest congeners is approximately 172 km to Phymaturus palluma, found to the south in the Province of Mendoza, and 90 km to Phymaturus aguanegra, located to the north in the Iglesia Department, Province of San Juan. The new record of P. williamsi is crucial for conservation efforts, as it highlights the need to assess and mitigate the impacts of mining activities in its habitat, ensuring the protection of this vulnerable species and its unique ecosystem. Further efforts are needed to explore new sites and search for additional P. williamsi populations to more accurately define the limits of its geographic range. However, considering the proximity of its congeners, we hypothesize that its distribution is highly restricted.